Model Aktualisasi “Manusia yang Lahir dari Allah” menurut 1 Yohanes 4:7 di Era Post Truth - Pangaribuan, Rosdinar (Sekolah Tinggi Teologi Kalvari Manado, 2023)
Abstract: Humans who are born from God are believers who continuously live in love with God's love. Because living in love is a command that must be actualized by believers as proof that they were born from God and know God. The person who has been born of God (1 John 2:29, 3:9, 5:1) is the person who brings God's love shining into the world. So based on 1 John 4:7